Basicranium and face: Assessing the impact of morphological integration on primate evolution. Issue 118 (May 2018) - Neaux, Dimitri; Sansalone, Gabriele; Ledogar, Justin A.; Heins Ledogar, Sarah; Luk, Theodora H.Y.; Wroe, Stephen
Abstract: The basicranium and facial skeleton are two integrated structures displaying great morphological diversity across primates. Previous studies focusing on limited taxonomic samples have demonstrated that morphological integration has a significant impact on the evolution of these structures. However, this influence is still poorly understood. A more complete understanding of craniofacial integration across primates has important implications for functional hypotheses of primate evolution. In the present study, we analyzed a large sample of primate species to assess how integration affects the relationship between basicranial and facial evolutionary pathways across the order. First, we quantified integration and modularity between basicranium and face using phylogenetically-informed partial least squares analyses. Then, we defined the influence of morphological integration between these structures on rates of evolution, using a time-calibrated phylogenetic tree, and on disparity through time, comparing the morphological disparity across the tree with that expected under a pure Brownian process. Finally, we assessed the correlation between the basicranium and face, and three factors purported to have an important role in shaping these structures during evolution: endocranial volume, positional behavior (i.e., locomotion and posture), and diet. Our findings show that the face and basicranium, despite being highly integrated, display significantly different evolutionary rates. However, our results demonstrate that morphological integration impacted shape disparity through time. We also found that endocranial volume and positional behavior are important drivers of cranial shape evolution, partly affected by morphological integration.